Instilling Islamic Educational Values at the Kafilul Yatim Quranic House in Bangun Rejo Village, Tanjung Morawa District - Friska Pratiwi; Mahariah; Khairuddin (ALSYS, 2026)
Although the moral degradation of younger generations in the digital era has received considerable scholarly attention, research examining how non-formal Islamic educational institutions can optimize their role in strengthening community spirituality remains limited. This study aimed to holistically examine the instillation of Islamic educational values at the Kafilul Yatim Qur’an House in Bangun Rejo Village. A qualitative approach was employed using primary data collected through structured non-participant observation, documentation, and structured interviews with educators, orphaned and non-orphaned students, and members of the fathers’ religious study group. The findings indicate that Islamic educational values were effectively transmitted across three learning domains: cognitive development through tajwid literacy, affective development through habituation based on Akhlāq lil Banīn, and psychomotor development through worship simulations. These values were instilled through an integrated combination of habituation, demonstration, storytelling and advice, expository lectures, oral assessment, and educational sanctions (tarhib). The study concludes that the effectiveness of non-formal Islamic education depends on the balanced integration of cognitive, affective, and psychomotor dimensions within value-oriented learning practices. This study contributes to the development of non-formal Islamic education by providing a conceptual and practical basis for reconstructing out-of-school religious curricula and fostering a Qur’anic family ecosystem within the community.